Innovation In-Building Coverage Solutions Based on Indoor Distributed Pico Base Stations and Their Application and Promotion - Wei Wei; Feng Zhou; Beijun Lu (Dianxin kexue)
Currently China Telecom is undergoing a crucial stage of LTE network deployment in a large scale. For Shanghai, the quality of in-building radio signals has a direct impact on the expansion of 4G network subscribers and the brand image of China Telecom in Shanghai. In this sense, how to enhance the in-building users experience in the 4G era is an important subject to be studied. From five perspectives“fast, intelligent, integrated, evolutionary and green”, the thoughts in designing innovative in-building coverage solutions based on indoor distributed pico base stations were demonstrated comprehensively, so as to help operators to quickly construct networks, manage them smartly and reduce the OPEX, as well as to enhance the network integration and to ensure smooth evolution.